Supporting consultation processes in preparation for the first GCARD conference : Final technical report - Staiger Rivas, Simone (International Center for Tropical Agriculture, 2010)
CIAT supported GFAR in designing and implementing the consultation processes related to the GCARD process and that culminated in the first Global Conference on Agricultural Research for Development (GCARD 2010) that was held in Montpellier in March 2010 as a first stage in what is envisaged as a progressive process of learning and feedback. The consultations were both on line and face to face and led by the regional fora. CIAT assured an overall input into the design and facilitation of those activities, as well as active support to those implementing consultation processes in the regions.